Application of Electro-Fenton/Bdd Process for Treating Tannery Wastewaters with Industrial Dyes - Salazar-Gonzalez, R (Elsevier B.V., 2017)
Degradation of the industrial dyes, Blue BR (BBR) 200 mg/L and Black TRS (BTRS) 100 mg/L, has been studied by the electro-Fenton/BDD process (EF/BDD). Each dye was tested in 0.05 mM Na2SO4 with 0.5 mM Fe2+ at pH 3.0 and in NaCl 0.05 mM, and electrolyzed in an undivided BDD/BDD flow reactor under galvanostatic conditions with 8, 15 and 31 mA/cm2. Dyes were oxidized via hydroxyl radicals ([rad]OH) formed at the BDD anode from water oxidation coupled with Fenton s reaction cathodically electrogenerating hydrogen peroxide (H2O2). Under Na2SO4 medium a 78% decolorization is achieved and an almost 90% under NaCl. Through the color abatement rate the dyes behavior was analyzed at the beginning of the oxidation process. Dissolved Organic Carbon (DOC) was tested to evaluate the degradation. From DOC removal, it was established an increasing relative oxidation power of the EF/BDD with respect to the supporting electrolyte Na2SO4 < NaCl, according with their decolorization trend. This study highlights the potential of the electro-Fenton/BDD process for the degradation of industrial dyes present in wastewaters under appropriate experimental conditions. © 2016 Elsevier B.V.
Keywords: EF/BDD; Industrial dyes; Wastewater treatment